Associations between dietary variety, portion size and body weight: prospective evidence from UK Biobank participants - Rochelle Embling (British Journal of Nutrition, 2023)
‘Dietary variety’ has been identified as a factor associated with food intake. Whilst this relationship may have longer-term benefits for body weight management when eating low-energy, nutrient-dense foods, it may increase the risk of overconsumption (and body adiposity) when foods are high energy density. This study sought to further explore pathways underpinning the relationship between dietary variety and body weight, by considering energy density as a moderating factor and portion size as a mediating factor in this relationship. Using prospective data from the UK Biobank, dietary variety scores, cumulative portion size, and energy density were derived from 24-hr dietary recall questionnaires at baseline and follow-up. Body mass index (BMI), whole-body fat percentage, and fat-free mass, were included as outcomes. Contrary to predictions, linear multiple regression models found some evidence of a negative, direct association between dietary variety scores and body weight outcomes at baseline (b = -.13). Though dietary variety was significantly associated with larger portions across timepoints (b = 41.86 – 82.64), a moderated mediation effect was not supported at baseline or follow-up (Index ≤ .035). Taken together, these findings provide population-level evidence to support a positive association between variety and food intake, which in turn has potential implications for body weight management, both in terms of moderating food intake and benefitting diet quality.